Blue Sukuk: Islamic finance instrument to promote blue economy - Ali, Mohammad Mahbubi; Haron, Razali (Routledge (Taylor & Francis Group), 2026)
This chapter examines the application of blue Sukuk as a Shariah-compliant financial instrument designed to promote the blue economy. Blue Sukuk offers an opportunity for global investors to fund projects focused on marine biodiversity preservation, renewable ocean energy, and sustainable fisheries. The chapter also sheds a critical light on the prospect of blue Sukuk in advancing SDGs, and identifies several key Shariah-compliant contracts and principles that can be employed in the structuring of blue Sukuk. The chapter concludes with a set of recommendations to enhance the adoption of blue Sukuk through robust regulatory frameworks, risk-sharing mechanisms, and greater market transparency.